Guidelines for Studying the Oxidative Stress Damage Model on Drosophila melanogaster - Quanyong Wu (Future Postharvest and Food)
ABSTRACT Oxidative stress contributes to cell aging and is implicated in diseases such as Alzheimer's disease, Parkinson's syndrome, atherosclerosis, and cancer. As a classic model for studying aging, Drosophila is also widely used in oxidative stress research due to its genetic tractability and physiological relevance. However, researchers often face challenges in selecting appropriate methods to characterize oxidative stress damage due to the diversity of available techniques and the complexity of oxidative stress mechanisms. To address this gap, this guideline provides a comprehensive summary of commonly used research methods for studying oxidative stress damage using Drosophila. It includes detailed explanations of basic principles and specific operating procedures, covering aspects such as lifespan analysis, ROS content, antioxidant enzyme activity, lipid peroxidation, protein oxidation, DNA damage, and inflammation levels. By offering an organized and practical reference, this guideline serves as a critical resource for researchers in method selection and experimental design, thus advancing the field of oxidative stress research.